Josef Steindl: An Economist of His Times - Shapiro, Nina (PSL Quarterly Review, 2012)
This paper discusses the life and work of Josef Steindl. It examines the development of his thought from his early writings on firm size and industrial concentration to his late work on the post-war problems of capitalist economies. Special attention is given to his seminal work on the Great Depression: Maturity and Stagnation in American Capitalism (1952). His work, which covered all the critical economic developments of the 20th century, greatly illuminated the problems of his times, and is as relevant to the problems of our own as it was to his. JEL Codes: E6, O4